The Relationship between Nursing Supervision and Completeness of Nursing Care Documentation in the Emergency Room at Dr. M.M Dunda Limboto Hospital, Gorontalo Regency - Nurliah, Nurliah; Syukur, Sabirin B; Talango, Sakinah (PROMOTOR, 2024)
Supervision is an important activity for managers which can influence improving the quality of nursing services, even health services in hospitals. One part of the implementation of supervision is the completeness of nursing care documentation which contains medical diagnoses, preparing treatment plans, carrying out assessments and evaluations that are prepared systematically, validly, and are morally and legally accountable. The research aims to analyze nursing supervision with complete documentation of nursing care. Quantitative research design with a cross-sectional approach. The population was 32 samples in the emergency room using a total sampling technique so the total sample was 32 people. The research results showed that the highest number of nursing supervision was good supervision, with 28 people with complete nursing documentation in the complete category, 21 people, pValue = 0.009 <0.05. Conclusion: There is nursing supervision with complete documentation of nursing care in the emergency room at RSUD dr. M.M. Dunda Limboto, Gorontalo Regency. It is hoped that the suggestions will become input for Dr. RSUD. M.M. Dunda Limboto in the quality of nursing services, especially in the completeness of nursing care documentation.